Perception and Motion in Real and Virtual Environments: A Narrative Review of Autism Spectrum Disorders - Valori, Irene; McKenna-Plumley, Phoebe E.; Bayramova, Rena; Farroni, Teresa (Frontiers in Psychology, 2021)
Atypical sensorimotor developmental trajectories greatly contribute to the profound heterogeneity that characterizes Autism Spectrum Disorders (ASD). Individuals with ASD manifest deviations in sensorimotor processing with early markers in the use of sensory information coming from both the external world and the body, as well as motor difficulties. The cascading effect of these impairments on the later development of higher-order abilities (e.g. executive functions and social communication) underlines the need for interventions that focus on the remediation of sensorimotor integration skills. One of the promising technologies for such stimulation is Immersive Virtual Reality (IVR). In particular, head-mounted displays (HMDs) have unique features that fully immerse the user in virtual realities which disintegrate and otherwise manipulate multimodal information. The contribution of each individual sensory input and of multisensory integration to perception and motion can be evaluated and addressed according to a user’s clinical needs. HMDs can therefore be used to create virtual environments aimed at improving people’s sensorimotor functioning, with strong potential for individualization for users. Here we provide a narrative review of the sensorimotor atypicalities evidenced by children and adults with ASD, alongside some specific relevant features of IVR technology. We discuss how individuals with ASD may interact differently with IVR versus real environments on the basis of their specific atypical sensorimotor profiles and describe the unique potential of HMD-delivered immersive virtual environments to this end.